Decoding Financial Sustainability in Microfinance: The Interplay of Financial Literacy and Leadership Trust - Esli Silalahi; Kornel Munthe; Miska Irani Tarigan; Riko Fridolend Sianturi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study empirically decodes the micro-level structural drivers determining the long-term financial sustainability of grassroots microfinance institutions, specifically savings and loan cooperatives in the North Sumatra region of Indonesia by uncoupling the dimensions of financial literacy. Design/methodology/approach – Utilizing a quantitative cross-sectional survey, data was collected from 276 active cooperative members. The hypothesized causal-predictive relationships were analyzed using Variance-Based Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results – Applied financial skills directly and significantly drive institutional sustainability. Financial knowledge indirectly enhances sustainability through the mediation of calculus-based institutional trust. Conversely, traditional financial culture fails to exert any significant direct or indirect effect on sustainability. Originality/Value – This research challenges the conventional reliance on informal social capital in microfinance. By evaluating individual financial literacy (knowledge and skills) alongside the environmental context of localized financial culture. The findings suggest that technical human capital (applied skills) and cognitively validated trust—rather than communal culture alone—serve as critical foundational components for grassroots financial resilience within the tested model.